Analisis Kebutuhan Materi Ajar pada Mata Kuliah Dasar-Dasar Pendidikan Jasmani SD bagi Mahasiswa PGSD - Nurhidayah; Roziah; Andreas Lubis (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Physical education plays an important role in supporting the physical, motor, social, emotional, health, and character development of students. Although physical education learning in elementary schools is generally carried out by subject teachers, students of the Elementary School Teacher Education Study Program (PGSD) as prospective classroom teachers still need to master the basic concepts of physical education to support healthy living habits and physical activity of students. This study aims to analyze the need for teaching materials in the Basics of Elementary School Physical Education course for PGSD students. The study used a quantitative descriptive approach with a survey method. The subjects of the study were PGSD students who had taken the Basics of Elementary School Physical Education course at Sari Mutiara Indonesia University Medan and Riau Islamic University. Data were collected using a needs analysis questionnaire that covered aspects of conceptual understanding, learning strategies, field practice, learning evaluation, character value integration, and teaching material development. The results showed that students had a very positive perception of the importance of the course. A total of 27.7% of respondents agreed and 70.9% strongly agreed that the Basics of Elementary School Physical Education material needs to be mastered by prospective elementary school teachers. The material with the highest level of need was the Nature and Basic Concepts of Physical Education (93.9%), while the Play Approach and PAKEM in Elementary School Physical Education Learning had the lowest percentage (43.2%). These findings indicate that students prioritize mastering basic concepts and practical skills. Therefore, the development of teaching materials needs to be tailored to student needs by strengthening concepts, practical experience, and linking theory and implementation of learning in elementary schools.